2021
DOI: 10.3389/fimmu.2021.716980
|View full text |Cite
|
Sign up to set email alerts
|

Brain Versus Blood: A Systematic Review on the Concordance Between Peripheral and Central Kynurenine Pathway Measures in Psychiatric Disorders

Abstract: ObjectiveDisturbances in the kynurenine pathway have been implicated in the pathophysiology of psychotic and mood disorders, as well as several other psychiatric illnesses. It remains uncertain however to what extent metabolite levels detectable in plasma or serum reflect brain kynurenine metabolism and other disease-specific pathophysiological changes. The primary objective of this systematic review was to investigate the concordance between peripheral and central (CSF or brain tissue) kynurenine metabolites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 176 publications
(237 reference statements)
0
35
0
Order By: Relevance
“…In contrast, kynurenine is considered a more robust marker of inflammation, as several pro-inflammatory cytokines, like CRP, IL-1β, IL-6, IL-8, TNF-α, and IFN-γ, were shown to enhance the activation of indoleamine 2,3-dioxygenase, increasing kynurenine levels, while the anti-inflammatory cytokines IL-4 and IL-10 counteracted this increase in kynurenine levels ( 50 54 ). Furthermore, kynurenine has previously been linked to obesity ( 57 ), cognitive aging ( 58 ), psychiatric disorders ( 54 , 55 , 59 ), brain volume loss ( 59 ), neurodegenerative disorders ( 60 ), and central nervous system injury ( 50 ). Taking into account the vast amount of evidence in the recent literature and considering our own results, we propose that kynurenine can be used as a generic peripheral inflammatory marker that is associated with neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, kynurenine is considered a more robust marker of inflammation, as several pro-inflammatory cytokines, like CRP, IL-1β, IL-6, IL-8, TNF-α, and IFN-γ, were shown to enhance the activation of indoleamine 2,3-dioxygenase, increasing kynurenine levels, while the anti-inflammatory cytokines IL-4 and IL-10 counteracted this increase in kynurenine levels ( 50 54 ). Furthermore, kynurenine has previously been linked to obesity ( 57 ), cognitive aging ( 58 ), psychiatric disorders ( 54 , 55 , 59 ), brain volume loss ( 59 ), neurodegenerative disorders ( 60 ), and central nervous system injury ( 50 ). Taking into account the vast amount of evidence in the recent literature and considering our own results, we propose that kynurenine can be used as a generic peripheral inflammatory marker that is associated with neuroinflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, kynurenine metabolites have been shown to induce dysregulation of glutamatergic pathways, leading to excitotoxic neural damage ( 56 ). The higher levels of kynurenine were associated with obesity ( 57 ), with cognitive decline in older adults ( 58 ) and with striatal and hippocampal volume loss in psychiatric disorders ( 59 ). In a model applying Alzheimer mouse, peripheral inhibition of the kynurenine pathway prevented neurodegeneration and memory deficits ( 60 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, for the metabolites traveling to the periphery over the BBB, extrapolation of the significance of KYN metabolization remains cumbersome. Illustratively, Skorobogatov et al (2021 ) describe a strong correlation between peripheral and central KYN concentrations in two studies ( Yuwiler et al, 1977 ; Haroon et al, 2020 ), while such interrelations remain absent for TRP itself. According to Yuwiler et al ( Yuwiler et al, 1977 ) and Curzon et al ( Curzon 1979 ), the observed CNS-periphery discrepancies in a mixed population of Huntington disease patients and healthy controls might be (partially) explained by the fact that most TRYCAT are known to bind circulating albumin (even with high affinity in case of TRP and KYN) and that only unbound (free) metabolites can enter the brain ( Cangiano et al, 1999 ).…”
Section: Introductionmentioning
confidence: 98%
“…The bulk of literature on TRYCAT in psychiatry concerns quantifying metabolite levels in peripheral blood as a proxy measure for central inflammatory processes. However, as summarized in a recent systematic review by Skorobogatov et al (2021) , only TRP and KYN and to some extent 3-HK fluently travel over the blood–brain barrier (BBB). It remains undefined whether peripheral production of non-crossing metabolites such as kynurenic acid (KA) and quinolinic acid (QUIN) could indirectly reflect central inflammatory processes, for instance, through induction by BBB-crossing macrophages or macrophage-secreted cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Immune-related aberrations are known to instigate and / or maintain neuropsychiatric disease states. 3 , 4 Thus, scrutinizing a batch of inflammatory markers for their potential in differential diagnostics is an auspicious and valid research strategy. Several metabolites of the kynurenine pathway have modulating effects on glutamatergic signaling, which in turn plays a role in the pathophysiology of psychiatric and neurological disease.…”
mentioning
confidence: 99%